2020
DOI: 10.1186/s12911-020-1108-1
|View full text |Cite
|
Sign up to set email alerts
|

A semi-supervised approach for extracting TCM clinical terms based on feature words

Abstract: Background: A semi-supervised model is proposed for extracting clinical terms of Traditional Chinese Medicine using feature words. Methods: The extraction model is based on BiLSTM-CRF and combined with semi-supervised learning and feature word set, which reduces the cost of manual annotation and leverage extraction results. Results: Experiment results show that the proposed model improves the extraction of five types of TCM clinical terms, including traditional Chinese medicine, symptoms, patterns, diseases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In this review, some studies reported that the application or combination of BERT could significantly improve the result of entity recognition or relation extraction [18,58,59,61]. In the last decade, the proposed deep learning models for IE tasks include BERT-convolutional neural network (CNN) [18], convolutional neural network with segment attention mechanism (SEGATT-CNN) [63], K-nearest neighbor (KNN) [53], long short-term memory (LSTM) [52,53], bidirectional long short-term memory (BiLSTM) [17], structural BiLSTM [31], LSTM-CRF [54,58], BiLSTM-CRF [22,28,55,58,62,64], BERT-BiLSTM-CRF [59,61,66], graph neural networks [21], and a nested NER model based on LSTM-CRF [29]. Among the above-mentioned models, the "BiLSTM-CRF" and "BERT-BiLSTM-CRF" have become popular deep learning models because of their good extraction performance: the BiLSTM model can capture more context information than the LSTM model.…”
Section: Deep Learning Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, some studies reported that the application or combination of BERT could significantly improve the result of entity recognition or relation extraction [18,58,59,61]. In the last decade, the proposed deep learning models for IE tasks include BERT-convolutional neural network (CNN) [18], convolutional neural network with segment attention mechanism (SEGATT-CNN) [63], K-nearest neighbor (KNN) [53], long short-term memory (LSTM) [52,53], bidirectional long short-term memory (BiLSTM) [17], structural BiLSTM [31], LSTM-CRF [54,58], BiLSTM-CRF [22,28,55,58,62,64], BERT-BiLSTM-CRF [59,61,66], graph neural networks [21], and a nested NER model based on LSTM-CRF [29]. Among the above-mentioned models, the "BiLSTM-CRF" and "BERT-BiLSTM-CRF" have become popular deep learning models because of their good extraction performance: the BiLSTM model can capture more context information than the LSTM model.…”
Section: Deep Learning Modelsmentioning
confidence: 99%
“…With this background, more approaches were explored to extract information from different types of TCM text data, and IE from TCM texts has shown encouraging improvements accordingly [17,18]. Although previous research has summarized some IE work in TCM [19][20][21], the new advanced technologies and emerging methods need to be further summarized and synthesized, for example, improved deep learning approaches and more types of extracted information [22,23]. In this study, we searched four literature databases for articles published from 2010 to 2021 that focused on the use of NLP methods to extract information from unstructured TCM text data.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many disciplines witness fast growth in exploiting machine learning and text mining technologies to discover knowledge hidden in a massive volume of data. Similarly, some efforts have raised in TCM which utilize machine learning and text mining technologies for discovering knowledge from prescriptions and clinical records, such as treatment rules mining [10,11], medical term extraction [12][13][14], syndrome differentiation [15], knowledge graph construction [16] and fine-grained entity corpus construction [17]. However, majority efforts in these studies are devoted to structured data or unstructured textual data written in modern Chinese language, in spite of the importance of ancient literature for modern TCM research and clinical practice, as mentioned in Section Background.…”
Section: Related Workmentioning
confidence: 99%
“…For the sentence-level labelling we employ the traditional metrics for the evaluation, including precision, recall, F 1 -value and accuracy. Specifically, for a tag i from { B , I , O }, the precision P i , recall R i , and F 1 -value F 1i are defined respectively in the formulas ( 12), ( 13) and (14).…”
Section: Datasets and Evaluation Metricsmentioning
confidence: 99%
“…Liu et al combined the BiLSTM-CRF model with semisupervised learning to reduce the cost of manual annotation and leveraged extraction results. e proposed method is of practical utility in improving the extraction of five types of TCM clinical terms, including traditional Chinese medicine, symptoms, patterns, diseases, and formulas [22]. Zhang et al worked on building a fine-grained entity annotation corpus of TCM clinical records [13].…”
Section: Introductionmentioning
confidence: 99%